Salmonella and tomatoes: Q & A for consumers - Max Teplitski; Keith Schneider; Michelle Danyluk (EDIS)
SL-263, a 6-page fact sheet by Max Teplitski, Keith Schneider, and Michelle Danyluk, provides research-supported answers to common consumer questions about the safety of fresh fruits and vegetables in response to the recent outbreak of salmonellosis linked to the consumption of tomatoes. Includes references. Published by the UF Department of Soil and Water Science, June 2008.